2021
DOI: 10.52973/rcfcv-e32086
|View full text |Cite
|
Sign up to set email alerts
|

Fibropapillomatosis in immature Green Turtles (Chelonia mydas) from the Gulf of Venezuela

Abstract: Fibropapillomatosis (FP) is affecting multiple marine turtle (MT) species worldwide. In Venezuela, the understanding about this neoplastic condition is still in early stage. Hence, this paper aims to assess the occurrence and frequency of FP in green turtles (GT) in the Gulf of Venezuela (GV). Herein, it was compiled and analyzed the reports in the database of the NGO ‘Grupo de Trabajo en Tortugas Marinas del Golfo de Venezuela’, which includes all records of stranded MT in the GV from 2000 to 2011. Between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
1
0
1
Order By: Relevance
“…Sea turtles with FP tumours appeared to be susceptible to entanglement in fishing lines and to have a reduced ability to swim and dive, locate, capture and swallow food and avoid predators (Chaloupka et al, 2008; Page‐Karjian, 2019). Immature turtles, mainly green turtles, are most frequently affected by FP on the coast of Campeche, as reported worldwide, and we agree on the need for further and more profound assessment of any association between habitat degradation and FP occurrence rates (Blackburn et al, 2021; Espinoza‐Rodríguez & Barrios‐Garrido, 2021; Silva‐Júnior et al, 2019).…”
Section: Discussionsupporting
confidence: 77%
“…Sea turtles with FP tumours appeared to be susceptible to entanglement in fishing lines and to have a reduced ability to swim and dive, locate, capture and swallow food and avoid predators (Chaloupka et al, 2008; Page‐Karjian, 2019). Immature turtles, mainly green turtles, are most frequently affected by FP on the coast of Campeche, as reported worldwide, and we agree on the need for further and more profound assessment of any association between habitat degradation and FP occurrence rates (Blackburn et al, 2021; Espinoza‐Rodríguez & Barrios‐Garrido, 2021; Silva‐Júnior et al, 2019).…”
Section: Discussionsupporting
confidence: 77%
“…Con respecto a los valores de leucocitos y heterófilos, los cuales son considerados como indicadores de estresores sistémicos para varios reptiles [10,36], éstos se mantuvieron dentro del intervalo referente documentado en individuos en la misma zona de estudio [21] y a su vez con valores promedios bajos como ha sido reportado en otras poblaciones a nivel global [37]. Sin embargo, los índices H:L (Heterófilos: Leucocitos) para poder describir o determinar algún estrés relacionado con los cambios de la edad y/o estadio con respecto a los cambios o exposición a estresores ambientales no pudo determinarse [37], debido a las numerosas limitantes que se presentaron en el estudio; como el tamaño/número de muestras, el acceso a los individuos examinados, logística en la colecta de muestras y elevados costos económicos para el procesamiento de algunas muestras [37,38,39].…”
Section: Resultados Y Discusiónunclassified
“…While some studies identified correlations with FP, results and conclusions vary. The most consistently reported correlation is that between FP prevalence and areas of reduced water quality (Adnyana et al, 1997; Chaloupka et al, 2009; dos Santos et al, 2010; Espinoza‐Rodríguez & Barrios‐Garrido, 2022; Foley et al, 2005; Hargrove et al, 2016; Herbst, 1995; Jones et al, 2016; Miguel et al, 2022; Van Houtan et al, 2014). Typically, these sites are associated with catchment outflow from areas with high anthropogenic influences like agriculture, urbanization, and/or industrialization.…”
Section: Introductionmentioning
confidence: 99%